1994
DOI: 10.1002/aic.690400214
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon catalyzes reactions of phenolics during liquid‐phase adsorption

Abstract: Variousphenolic compounds in aqueous buffer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 6 publications
2
45
0
1
Order By: Relevance
“…The phenol adsorption capacity of AC-M was found to be similar to that of the most active carbons reported in the literature [12,18,20]. It should be noted that this isotherm was obtained in oxic conditions so the adsorption capacity may be overestimated because of the effect of phenol coupling [21]. It has been found that if dissolved oxygen is present in the solution, phenol can polymerise to form long chains, which apparently increases the retention capacity.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…The phenol adsorption capacity of AC-M was found to be similar to that of the most active carbons reported in the literature [12,18,20]. It should be noted that this isotherm was obtained in oxic conditions so the adsorption capacity may be overestimated because of the effect of phenol coupling [21]. It has been found that if dissolved oxygen is present in the solution, phenol can polymerise to form long chains, which apparently increases the retention capacity.…”
Section: Resultsmentioning
confidence: 48%
“…Subsequently, the active carbon was weighed to measure the loss due to oxidation. In addition, the isotherm of phenol adsorption onto the AC-M was obtained at 208C (AE28C) following a standard procedure described elsewhere [21].…”
Section: Methodsmentioning
confidence: 99%
“…Highest affinity with sorbates is thus not always desirable because it may decrease their ability for regeneration. The surface groups of AC can enhance oxidative coupling of organic molecules (aromatic hydrocarbons) to form aromatic oligomers, which irreversibly adsorbed on the carbon surface [92][93][94][95]. Hence, the design of optimal AC adsorbents should provide suitable textural properties and surface groups.…”
Section: Adsorptionmentioning
confidence: 99%
“…The highest phenol feed concentration of 10 g/ L not only suppressed the carbon combustion providing short saturation time (2 h) and densely crowed phenol surface, but also produced a considerable irreversible weight gain as reported above. Activated carbon is well known to catalyse phenol coupling reactions [92][93][94][95] forming condensation products that can strongly adsorb onto the carbon. Not surprisingly, a batch study testing the CI carbon on phenol WAO [61] deduced from liquid and gas phase carbon balances the deposit of important amounts of carbonaceous matter on the carbon surface.…”
Section: Catalystmentioning
confidence: 99%
“…Recientemente se ha dado énfasis a la reactividad química de la superficie del carbón activado, ya que se ha demostrado que estos carbones catalizan varias reacciones de oxidación, reducción, halogenación, deshidrogenación, polimerización y sustitución nucleofílica, entre otras [1][2][3][4][5]. Se ha reportado que la reactividad de los carbones está directamente relacionada con sus propiedades químicas.…”
Section: Introductionunclassified